Análise genômica de bactérias probióticas bacteriocinogênicas: identificação taxonômica e caracterização de genes relacionados à síntese de bacteriocinas. - Oliveira, Mauro de Medeiros (Universidade Estadual Paulista (Unesp), 2025)
This study aims to perform a genomic analysis of probiotic bacterial strains producing bacteriocins, isolated from gut microbiota samples of Cobb broiler chickens (Gallus gallus domesticus), crossbred Landrace and Large White pigs (Sus scrofa domesticus), and fish (Nile tilapia, Oreochromis niloticus, and rainbow trout, Oncorhynchus meu beijo). To achieve this, the following specific objectives will be achieved: (1) Perform genomic sequencing after isolation and phenotypic characterization of bacteriocin-producing lactic acid bacilli (LAB) strains. (2) Perform comparative genomics by phylogenetic analysis of 16S rRNA and sequence type (MLST) obtained in silico. (3) Identify bacteriocin genes using different databases and bioinformatics tools such as AntiSMASH, BACTIBASE, BAGEL, BOA, and NeuBI. The aim is to discover new bacteriocin variants and their association with specific strains, species, and ecological niches. Once the strains are genomically specified, the project aims to contribute to the rational development of probiotic supplements for livestock.
Genomic analysis of bacteriocinogenic probiotic bacteria: taxonomic identification and characterization of genes related to the synthesis of bacteriocins.
N/D
Keywords: Bacteriocinas; Genômica comparativa; Metagenômica; Probióticos; Análise de sequência de DNA